Metodologia de investigacion en entomologia de frijol - Cardona, C.; Zuniga, T (United Nations Development Programme, 1985)
The general objectives of CIAT's bean entomology program are mentioned. The 1st priority has been given to var. resistance as an ideal pest control method. At CIAT's headquarters (Palmira, Colombia), studies are conducted on Empoasca kraemeri, mites, and storage insects; var. resistance to Apion godmani and Epinotia aporema is being studied at other institutions. The steps of genetic improvement of beans for resistance to E. kraemeri are described: selection of sources of resistance, hybridization of selected materials, and selection of resistant progenies. (CIAT)